Depth of invasion of oral squamous cell carcinoma in Nos2-knockout mice correlated to alterations in systemic inflammatory markers following 4NQO treatment - Santos, Débora de Oliveira; Costa, Anaíra Ribeiro Guedes Fonseca; Duarte, Pedro Victor Silva [UNESP]; Pitorro, Tássio Edno Atanásio; Fonseca, Lúbia Cristina; Cardoso, Sérgio Vitorino; de Faria, Paulo Rogério; Loyola, Adriano Mota (Wiley, 2024)
Background: Peripheral blood analysis is a non-invasive and low-cost technique of prognostic value for several diseases, including oral cancer. Considering the role of inducible nitric oxide synthase in tumor-associated inflammation, this study purposed to evaluate the influence of this enzyme on peripheral blood parameters and systemic inflammatory biomarkers during murine oral carcinogenesis. Methods: A 50 μg/mL solution of 4-nitroquinoleine-N-oxide was provided to 15 C57BL/6J (Nos2+/+) and 16 B6.129P2-Nos2tm1Lau/J (Nos2−/−) for 16 weeks. Animals were followed for 8 weeks after treatment. Blood samples and tongues were collected for hematological and histopathological analyses. Red blood cells, white blood cells, and platelet cell parameters were analyzed. The neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and the systemic immune-inflammation index were also calculated. The depth of invasion of all carcinomas was measured. Results: Differences were found in several blood parameters. The depth of invasion in Nos2−/− was lower than in Nos2+/+ (p = 0.009), and strong correlations were found between depth of invasion and neutrophil count (ρ = −0.68, p = 0.017), lymphocyte count (ρ = 0.72, p = 0.011), neutrophil-to-lymphocyte ratio (ρ = −0.65, p = 0.025), platelet-to-lymphocyte ratio (ρ = −0.73, p = 0.013), and systemic immune-inflammation index (ρ = −0.67, p = 0.037) in Nos2−/− mice. Conclusion: Inducible nitric oxide synthase seems to have an important role in OSCC invasion and progression, which might be associated to alterations in immune-inflammatory cell dynamics evidenced by peripheral blood and systemic inflammatory biomarkers.
Keywords: carcinogenesis; hematological tests; nitric oxide; oral cancer; tumor biomarkers